2017
DOI: 10.3389/fnut.2017.00009
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Volumetric Absorptive Microsampling Coupled with Stable Isotope Dilution Assay and Liquid Chromatography–Tandem Mass Spectrometry as Potential Diagnostic Tool for Whole Blood 5-Methyltetrahydrofolic Acid

Abstract: Volumetric absorptive microsamplers (VAMS) have been developed recently as a promising tool for clinical blood sampling. Compared to dried blood spot samples analyzed by accurate stable isotope dilution assays (SIDAs), the new technique could provide further substantial miniaturizing of folate assays by eliminating hematocrit effects and uneven analyte distribution within the sample. Herein, we present a miniaturized SIDA coupled with LC-MS/MS measurement of 5-methyltetrahydrofolic acid as main folate vitamer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Several Proof-Of-Concept studies can be found in literature, demonstrating the usefulness of VAMS devices for various compounds and purposes, including the analysis of caffeine, paraxantine, steroid compounds, 5-methyltetrahydrofolic acid, hydroxyurea, natural and synthetic cannabinoids, cocaine and metabolites, oxycodone and metabolites, asenapine enantiomers and iron isotopes [35,[42][43][44][45][46][47][48]. To date, there are no studies on reliability of VAMS technique for the analysis of antidepressant concentrations, neither on blood nor on OF.…”
Section: Discussionmentioning
confidence: 99%
“…Several Proof-Of-Concept studies can be found in literature, demonstrating the usefulness of VAMS devices for various compounds and purposes, including the analysis of caffeine, paraxantine, steroid compounds, 5-methyltetrahydrofolic acid, hydroxyurea, natural and synthetic cannabinoids, cocaine and metabolites, oxycodone and metabolites, asenapine enantiomers and iron isotopes [35,[42][43][44][45][46][47][48]. To date, there are no studies on reliability of VAMS technique for the analysis of antidepressant concentrations, neither on blood nor on OF.…”
Section: Discussionmentioning
confidence: 99%
“…VAMS devices contain a polymeric tip that absorbs a fixed volume of whole blood, independent of the Hct (40,41). In 2017, Kopp and Rychlik described the determination of 5methyltetrahydrofolic acid (5-MTHF) in VAMS samples (42). Even though analysis of whole DBS and VAMS samples eliminates the Hct-based area bias, the extraction efficiency of analytes from dried samples may still be impacted by the Hct.…”
Section: Hct Effectmentioning
confidence: 99%
“…Folate concentrations substantially decreased when samples were stored at higher temperature (24-27°C) and greater humidity (53-68%). Kopp and Rychlik evaluated the short-term stability of 5-MTHF in both DBS and VAMS samples (42,66). 5-MTHF in VAMS samples was stable during 2.5h drying at RT.…”
Section: Stabilitymentioning
confidence: 99%
“…23 More recently, Kopp and Rychlik evaluated the stability of the main folate vitamer 5-methyltetrahydrofolate (5MTHF) in DBS and VAMS samples using liquid chromatography tandem mass spectrometry (LC-MS/ MS). 24,25 However, only stability at −20 °C and the effect of drying on VAMS samples was included and no evaluations were done at room or higher temperatures. Thus, based on the available data, it remains unclear whether the observed stability is adequate to perform e.g., home-sampling studies.…”
Section: Introductionmentioning
confidence: 99%